-3(2x+2)=-24

Simple and best practice solution for -3(2x+2)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x+2)=-24 equation:


Simplifying
-3(2x + 2) = -24

Reorder the terms:
-3(2 + 2x) = -24
(2 * -3 + 2x * -3) = -24
(-6 + -6x) = -24

Solving
-6 + -6x = -24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -6x = -24 + 6

Combine like terms: -6 + 6 = 0
0 + -6x = -24 + 6
-6x = -24 + 6

Combine like terms: -24 + 6 = -18
-6x = -18

Divide each side by '-6'.
x = 3

Simplifying
x = 3

See similar equations:

| -13=24+5(x-3.4) | | -8y+10=-7y | | 2z^2+2z+1=0 | | 56x-8=12-3x | | 148=64+6x | | 2y+5-y=-3(y-6) | | (2+4)+4(383949+73838)= | | 6x-9-4x+2= | | w*4.7+(1-w)*11.8=10 | | 3(175x+152)=2,556 | | 10-5(x-6)=115 | | -2sin^2(x)+3cos(x)+3=0 | | (3+b)*(3-b-a-2)+(a-1)*(b-1)= | | 4(4x-3)=12 | | 18(4-3x)=162 | | 30+00.20=94 | | 464+7p=700 | | 30+20=94 | | 5w+11=-19+11w | | 3(2x+4y)=12 | | 6+f=11 | | -25+y=65 | | 5x+25y=465 | | 8.4+0.1n=8.81 | | 12x+8=116 | | 2(x+4)+2x=116 | | Y+12=15 | | -2(x+2)+2=10 | | 35q=-172 | | -12t=-2t-20 | | .65x=40 | | 3+c=19 |

Equations solver categories